1963
DOI: 10.1001/archneur.1963.00460060021002
|View full text |Cite
|
Sign up to set email alerts
|

The H Reflex in Normal, Spastic, and Rigid Subjects

Abstract: The H reflex has been widely used in the study of human physiology, both normal 3,6,11,13,18,19 and abnormal.12,14,15,16,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0
1

Year Published

1964
1964
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(84 citation statements)
references
References 10 publications
(1 reference statement)
6
70
0
1
Order By: Relevance
“…20,21 Electrophysiologic parameters are objective but there is some controversy regarding the usefulness of these parameters in evaluating spasticity. Although both H/M ratio and F/M ratio have been reported to assess either the spinal segmental re¯ex or excitability of the anterior horn cells, 22,23 there are studies reporting that they were increased in subjects with decreased muscle stretch re¯ex. 24,25 Little et al 26 reported that these ratios were useful methods in evaluating spasticity when measured serially.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Electrophysiologic parameters are objective but there is some controversy regarding the usefulness of these parameters in evaluating spasticity. Although both H/M ratio and F/M ratio have been reported to assess either the spinal segmental re¯ex or excitability of the anterior horn cells, 22,23 there are studies reporting that they were increased in subjects with decreased muscle stretch re¯ex. 24,25 Little et al 26 reported that these ratios were useful methods in evaluating spasticity when measured serially.…”
Section: Discussionmentioning
confidence: 99%
“…10 One measure used by numerous investigators to quantify hyper-reflexia is the electrical analogue of the classic tendon jerk reflex, referred to as the Hoffman or H-reflex. 2,[15][16][17][18][19] The H-reflex is a compound electromyographic (EMG) response elicited by the synaptic activation of motoneurons by muscle afferents following stimulation of muscle nerves. Thompson et al 20 investigated four measures of H-reflex excitability in a contusion model of SCI in the rat.…”
Section: Introductionmentioning
confidence: 99%
“…Previous comparisons of the H reflex amplitude in normal and rigid subjects have failed to show any abnormality (Angel and Hofmann, 1963;Dietrichson, 1971) but the AJ/H response ratio was found to be increased by Dietrichson (1971) despite normal H responses and the fact that the mechanical threshold of rigid subjects was normal. In the latter study, the control subjects were considerably younger than the patients and the measured maximal AJ and H amplitudes were given, rather than the ratio between the mean of a series of H responses and the M response.…”
Section: Tonic Activation: Resultsmentioning
confidence: 99%